'The current gold coin of the New Jerusalem': perception, symbolization, and money in Hawthorne's The Scarlet Letter. Issue 2 (4th March 2017) - Dietrick, Jon
ABSTRACT: As an external visual marker of what is supposed by other characters in the novel as its wearer's 'internal, ' spiritual state, Hester Prynne's Scarlet 'A' is, among other things, an emblem of a powerful American anxiety regarding the gulf between appearance and reality, symbol and meaning. The desperate and dangerous need for fixed signs and self-evident identities that obsesses Hawthorne's Puritan-era characters is directly related to the gold-paper money debates that dominated the politics of Hawthorne's own time, with their concern for issues of 'character' and value and what we might now call the gap between the symbolic and the real, or face value and material value.